PELATIHAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA UNTUK UMKM D’KRIUK DIWILAYAH CIBUBUR JAKARTA TIMUR - Rainisa, Fadia; Rahayu, Narsih; Puspitasari, Novita Maryati; Rahmadi, Zara Tania (ASOSIASI IDEBAHASA KEPRI, 2025)
This simple accounting training aims to improve the understanding and skills of MSMEs, especially Ayam D’kriuk in Cibubur, in recording and managing finances. Activities include basic accounting theory and the practice of recording transactions, preparing journals, ledgers, profit and loss reports, and balance sheets. With more systematic financial reports, business actors can make better business decisions and increase access to funding.